GERMANIUM ISOTOPE MEASUREMENTS OF HIGH-TEMPERATURE GEOTHERMAL FLUIDS USING DOUBLE-SPIKE HYDRIDE GENERATION MC-ICP-MS - Siebert C.; Ross A.; McManus J. (My University, 2006)
We present a double-spike isotope dilution MC-ICP-MS technique for the determination of germanium (Ge) isotope fractionation. Using this technique we determined Ge isotope compositions of geothermal spring fluids, a Columbia River Basalt sample, and an in-house diatom standard. Our technique uses a 73Ge/70Ge double spike in combination with hydride generation for Ge extraction from the sample matrix. Fractionation is determined on the 74Ge/72Ge mass ratio. The double spike allows us to effectively correct analytical isotope fractionation. Our external standard reproducibility is 0.4? (2 SD) over the course of several months. The minimum quantity of Ge needed for isotope analysis is approximately 2 ng. Consistent with previous work on geothermal fluids, Ge in the geothermal spring samples presented here is enriched over Si as compared to low temperature weathering signatures. This observation is typically interpreted as Ge exclusion during silicate mineral precipitation (e.g., quartz). Our isotope results indicate that the analyzed high temperature fluids fractionate Ge isotopes with a range in ?74Ge between -0.4? and -1.4? relative to a Columbia River basalt. We cautiously interpret the observed fractionation as preferential removal of heavy Ge isotopes out of solution during cooling of the hydrothermal fluid and subsequent precipitation of quartz. ? 2006 Elsevier Inc. All rights reserved.
Keywords: GERMANIUM; HYDROTHERMAL FLUID; INDUCTIVELY COUPLED PLASMA METHOD; ISOTOPIC COMPOSITION; ISOTOPIC FRACTIONATION; MASS SPECTROMETRY; BACILLARIOPHYTA